Validation of the APP23 Transgenic Mouse Model of Alzheimer’s Disease through Evaluation of Risperidone Treatment on Aggressive Behaviour - Vloeberghs, Ellen; Coen, Katrien; Dam, Debby Van; Deyn, Peter Paul De (Arzneimittelforschung, 2008)
Valid animal models are indispensable in the drug discovery pipeline for dementia. Transgenic APP23 mice model Alzheimer’s disease patients’ memory deficits and additionally present with various behavioural disturbances, such as aggressive behaviour. The present study investigated and confirmed significant sensitivity of the model to the aggression-lowering ability of the antipsychotic agent risperidone (CAS 106266-06-2). The sensitivity for such anti-aggressive action contributes to the therapeutic predictive validity of the APP23 model of Alzheimer’s disease, which can be used as a pre-clinical screening tool for the identification of novel anti-aggressive agents.
Keywords: Aggressive behaviour; Alzheimer’s disease; Antipsychotic agents; CAS 106266-06-2; Risperidone, aggression-lowering ability, transgenic mouse model; Transgenic mouse model, validation